Balkan Rhapsodies: 78 Measures of War - Silva, Jeff (Eye Wash Production, 2008)
Verzio FF Submission An "episodic documentary poem" that interweaves a mosaic of encounters, observations, and reflections from the director's travels throughout war-torn Serbia and Kosovo between 1999 and 2005. Using the 78 days of NATO bombings (March 24 - June 10, 1999) as a structural reference point, this documentary infuses the fragmentation, cultural incongruities and ultimate dissolution of the former Yugoslavia into the fabric of its editing through a poetic assemblage of 78 episodic movements (measures). "Balkan Rhapsodies" deftly balances a serious and humorous landscape that captures the essence of life in the Balkan's of a generation ensnared in war during the Milosevic years.